2016
DOI: 10.18632/oncotarget.13945
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal marker expression is elevated in Müller cells exposed to high glucose and in animal models of diabetic retinopathy

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 35 publications
5
17
0
Order By: Relevance
“…Gliotic altered Müller cells have increased GFAP immunoreactivity under pathological conditions [ 23 ]. We further investigated the expression level of the GFAP protein in the TAA-injected rats by immunohistochemistry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gliotic altered Müller cells have increased GFAP immunoreactivity under pathological conditions [ 23 ]. We further investigated the expression level of the GFAP protein in the TAA-injected rats by immunohistochemistry.…”
Section: Resultsmentioning
confidence: 99%
“…Gliotic alterations of Müller cells include cellular hypertrophy and proliferation [ 33 ]. Upregulation of GFAP is known to be a very sensitive early indicator of retinal stress [ 23 ]. In the present study, we showed that GFAP was highly expressed in the retinas of the TAA-injected rats with hepatic retinopathy, indicating a predominant Müller cell gliosis.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycemia promotes release of (1) growth factors, such as vascular endothelial growth factor (VEGF) and pigment epithelium-derived factor (PEDF), and (2) cytokines and chemokines including interleukin-1β (IL-β), interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), and chemokine ligand-2 (CCL2)[52,5561] [6264]. In vitro studies have provided ample evidence that Müller cells are a potential source for growth factors and cytokines when stimulated with elevated glucose levels.…”
Section: Release Of Growth Factors and Pro-/anti-inflammatory Cytokinmentioning
confidence: 99%
“…Moreover, the oral administration of an inhibitor of aldose reductase (sorbinil) prevented gliotic changes. An increase in retinal vimentin expression was observed in STZ‐induced diabetic rats, in MGCs cell cultured under high glucose conditions and in epiretinal membranes of diabetic patients (Zhou et al., ).…”
Section: Gliosismentioning
confidence: 99%